A multimodal approach to cancer-related cachexia: from theory to practice. Issue 8 (3rd August 2021) - Avancini, Alice; Trestini, Ilaria; Tregnago, Daniela; Lanza, Massimo; Menis, Jessica; Belluomini, Lorenzo; Milella, Michele; Pilotto, Sara
ABSTRACT: Introduction : Cachexia represents a relevant issue in oncological care, which is still lacking effective therapies. Although the incidence of cancer cachexia varies across cancer types, it is responsible for approximately a quarter of cancer-related deaths. The pathophysiology of this syndrome is multifactorial, including weight loss, muscle atrophy and impairment of the pro-/anti-inflammatory balance. Areas covered : Diagnostic criteria and optimal endpoints for cachexia-dedicated trials are still debated, slowing the identification of interventions counteracting cachexia sequaele . The multifaceted features of this syndrome support the rationale for personalized therapy. A multimodal approach is likely to offer the best option to address key cachexia-related issues. Pharmacologic agents, physical exercise, nutritional and psycho-social interventions may have a synergistic effect, and improve quality of life. Expert opinion : A personalized multimodal intervention could be the best strategy to effectively manage cancer cachexia. To offer such a comprehensive approach, a specialized staff, including health professionals with different expertise, is necessary. Each specialist plays a specific role inside the multimodal intervention, with the aim of delivering the best cancer care and access to the most effective therapeutic options for each patient.